(3SjGSI fbOjI ZjQ JbdjOjI dJfTjW GdGbJUGO Gdbhejs - (3QeRj(B, (3eMehOs ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s, 2019)
(3JfGhd gPG GdcJGH ehVhY GdJjSjQ Gdcej, MjK bOe ef NdGd aUhd OQGSJg GWdGdg Ydi GdSjGSGJ GdJj JJHYgG GdMcheGJ dJfTjW GdGbJUGO Gdbhej, HGdGVGaI Gdi GdSjGSI GdfbOjI hSjGSI GdJjSjQ Gdcej aj ChQhHG haj GdjGHGf haj GdUjf haj GdOhd GdfGTFI, hGdOaYI GdChdi hGdKGfjI hGdKGdKI ef GdJjSjQ Gdcej GdCeQjcj (B.s
(3HHdjhZQGajG U(B.257s
Keywords: (3GdJjSjQ Gdcejs; (3GdSjGSGJ GdGbJUGOjIs; (3GdSjGSI GdfbOjIs